Quality Control of Packaged Drinking Water (AMDK) Products : (Case Study: CV. Tirta Sasmita) - Besse Arnawisuda Ningsi; Fince Rauna Rehi Bota (Jurnal Teknologi dan Manajemen Industri Terapan, 2026)
The quality of bottled drinking water (AMDK) has now begun to decline, prompting public complaints about dirty water, bad taste, and other issues. This study aims to analyze the quality control of bottled drinking water (AMDK) products at CV. Tirta Sasmita with product defects that still frequently occur, such as incomplete water, leaks, damaged cups, bad water, machine rejects, damaged cartons, damaged lids, and to determine what factors cause these defects in the production process. The method used is the Total Quality Management (TQM) approach and the six sigma DMAIC stage (Define, Measure, Analyze, Improve, and Control) with an analysis of 220 ml AMDK production data in the period January 2024 - January 2025. The results of the study show a total production of 38,462 per unit with a number of defective products of 6,582 per unit. The dominant defect type is the leak defect, at 2,328 per cup. Analysis using a proportion control chart (p-chart) shows that most processes remain within the control limits, but several points are outside the limits, indicating instability in the production process. The main causes of defects come from machines, human resources, methods, and materials. From this study, quality control at CV. Tirta Sasmita is not yet fully stable. Therefore, the company is advised to conduct regular machine maintenance and enhance quality oversight to improve the quality of AMDK products and minimize defects.